Influence of Parenting Styles on Students’ Academic Performance for Education Quality Assurance in Some Selected Secondary Schools in Katsina Metropolis - Bada, Steve Olusegun; Pwajok, Martha A. (International Journal of Educational Management, 2022)
The issue of parenting styles has been highlighted as a major component of academic achievement among students of secondary school. This is because, there is a belief that each parenting style sets its own demands with respect to the conduct of learners and standards that they have to meet. The researcher in this work tries to investigate “the influence of parenting styles on students’ academic performance for education quality assurancein some selected secondary school in Katsina Local Government Area of Katsina State, Nigeria”. Three parenting styles where considered among the existing once and three research hypotheses to guide the study was formulated by the researcher. Two hundred (200) copies of questionnaire were administered to Two hundred (200) sampled students from four (4) selected secondary schools to generate data. Their responses were tallied and put in frequency tables and the Pearson Product Moment Correlation Co-efficient (r) was used for the analysis. The findings indicated the following: There is weak negative insignificant relationship between democratic and autocratic parenting styles and students’ academic performance in secondary schools whereas laissez-faire parenting styles enjoys an insignificant positive relationship between and students’ academic performance in secondary schools in Katsina Metropolis.. On these grounds, it was concluded that parenting styles have some measure of influence on the academic performance of secondary school children. For further studies and necessary action, some recommendations were made.